STUDI REKAHAN PADA TEROWONGAN KERETA API DENGAN METODE GROUND PENETRATING RADAR (GPR) (STUDI KASUS DI DAERAH SASAKSAAT) PADALARANG JAWA BARAT - Syahril Syahril (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
Ground Penetrating radar (GPR) is a geophysical method that uses electromagnetic wavepropogation and has a high resolution towards dielectric contrast in rocks. In this paper, the method is radarreflection profiling and data prosessing by using software Reflex W Test Version. In situ measurement ofelectromagnetic was carried out by georadar method using Ramac GPR at frequency of 200 MHz in side oftunnel. The result of the measurement indicate there are many joint in the concrete of tunnel wall it trademark carbonate calsite in the stone.Key words: joint, GPR, tunnel